Plasma immersion low-energy-ion bombardment of naked DNA - Sarapirom S. (2014)
Low-energy ion irradiation of DNA is of great interest in fundamental studies on mechanisms involved in low-energy ion beam induced mutation, plasma sterilization and ionizing radiation risk of lives. We have made the first attempt to use low-energy ions in plasma immersion ion implantation and deposition (PIII-D) to bombard naked plasmid DNA to investigate effect on the DNA structural modification and mutation. Naked DNA samples were immersed in either argon or nitrogen plasma in low pressure and then bombarded by ions in the plasma in different conditions, namely, using a low bias of -2.5kV, or no bias, in which the sample holder was either grounded or not grounded, to low fluences of 1011, 1012 and 1013ions/cm2. The plasma-treated DNA was transferred into bacteria E. coli. Mutation was found from the bacterial colonies when DNA was bombarded with the bias, but not found when DNA was bombarded without a bias. This indicates that ions with energy only at the order of the thermal energy cannot induce mutation but with low-energy of keV the ions can. Subsequent gel electrophoresis and DNA sequencing analyzed the DNA structural changes and found certain modifications in the DNA forms. © 2010 Elsevier B.V.